Autotaxin and soluble IL-2 receptor concentrations in cerebrospinal fluids are useful for the diagnosis of central nervous system invasion caused by haematological malignancies - Shimura, Takuya; Kurano, Makoto; Morita, Yoshifumi; Yoshikawa, Naoyuki; Nishikawa, Masako; Igarashi, Koji; Shimamoto, Satoshi; Aoki, Junken; Yatomi, Yutaka (Annals of clinical biochemistry, 2019)
Invasion of the central nervous system by haematological malignancies is diagnosed by cytological analyses of cerebrospinal fluid or diagnostic imaging, while quantitative biomarkers for central nervous system invasion are not available and needed to be developed. In this study, we measured the concentrations of autotaxin and soluble IL-2 receptor in cerebrospinal fluid and evaluated their usefulness as biomarkers for central nervous system invasion. We observed that both the autotaxin and soluble IL-2 receptor concentrations in cerebrospinal fluid were higher in subjects with central nervous system invasion than in those without, and the cerebrospinal fluid concentrations were independent from the serum concentrations of these biomarkers. ROC analyses revealed that the soluble IL-2 receptor concentration in cerebrospinal fluid was a strong discriminator of central nervous system invasion in subjects with haematological malignancies, while the autotaxin concentration in cerebrospinal fluid also had a strong ability to discriminate central nervous system invasion when the subjects were limited to those with lymphoma. The combined measurement of autotaxin and soluble IL-2 receptor in cerebrospinal fluid improved the sensitivity without notably reducing the specificity for central nervous system invasion in subjects with lymphoma when central nervous system invasion was diagnosed in cases where either value was beyond the respective cut-off value. These results suggest the possible usefulness of soluble IL-2 receptor and autotaxin concentrations in cerebrospinal fluid for the diagnosis of central nervous system invasion.